Implementasi Fondrakö Si Lima Ina Sebagai Dasar Penentuan Jujuran Adat Perkawinan di Banua Dangagari Desa Sitolubanua Fadoro Kecamatan Moro’ö Kabupaten Nias Barat - Gulo, Melvin Nur Oktaviani; Harefa, Anugerah Tatema; Harefa, Hendrikus O. N.; Bawamenewi, Adrianus (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the implementation of Fondrakö Si Lima Ina as a basis for determining the honesty of marriage customs in Banua Dangagari, Sitolubanua Fadoro Village, Moro'o District, West Nias Regency, and to find out why the implementation of the böwö system was still complained about by some people when Fondrakö Si Lima Ina became basis for determining the fairness of marriage customs. This research uses a qualitative method with a descriptive approach. The research instrument is the researcher himself, who takes data using a cellphone as a recording tool, drawings and notebooks. Data collection techniques are interviews, observation and documentation. The results of the research are: first, implementation of Fondrakö Si Lima Ina as a basis for determining the honesty of marriage customs, especially in Banua Dangagari, based on the norm values ​​in Fondrakö Si Lima Ina. Second, the implementation of the Honesty system is still complained about by some Nias people when Fondrakö Si Lima Ina determines the honesty of marriage customs because the amount of böwö that must be paid by the groom to the bride is determined based on traditional position.